2016
DOI: 10.1007/s00253-016-8032-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens SC06 alleviates the oxidative stress of IPEC-1 via modulating Nrf2/Keap1 signaling pathway and decreasing ROS production

Abstract: Oxidative stress (OS) plays a major role in the gastrointestinal disorders. Although probiotics were reported to repress OS, few researches compared the antioxidant ability of different Bacillus strains and deciphered the mechanisms. To select a Bacillus strain with higher antioxidant capacity, we used HO to induce intestinal porcine epithelial cell 1 (IPEC-1) OS model. The most suitable HO concentration and incubation time were determined by the half lethal dose and methyl thiazolyl tetrazolium. Correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 55 publications
11
103
0
Order By: Relevance
“…Consistent with this, research in humans have shown an increased erythrocyte SOD and GPx activities as well as total antioxidant status in type 2 diabetic patients receiving yogurt containing Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 [57]. Furthermore, our previous in vitro research also implied that Bacillus amyloliquefaciens SC06 elevated CAT and GST gene expressions and the CAT activity in intestinal porcine epithelial cells-1 (IPEC-1) [7]. …”
Section: Modes Of Action Of Probiotic Bacteria In Antioxidationsupporting
confidence: 52%
See 3 more Smart Citations
“…Consistent with this, research in humans have shown an increased erythrocyte SOD and GPx activities as well as total antioxidant status in type 2 diabetic patients receiving yogurt containing Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 [57]. Furthermore, our previous in vitro research also implied that Bacillus amyloliquefaciens SC06 elevated CAT and GST gene expressions and the CAT activity in intestinal porcine epithelial cells-1 (IPEC-1) [7]. …”
Section: Modes Of Action Of Probiotic Bacteria In Antioxidationsupporting
confidence: 52%
“…According to their findings, treatment with MIYAIRI 588 elevated hepatic antioxidant enzyme activities in (CDAA)-defined-diet-induced rats via the activation of Nrf2 expressions [65]. Additionally, recent evidence obtained by our research group also demonstrated that probiotic Bacillus amyloliquefaciens SC06 ameliorated the H 2 O 2 -induced IPEC-1 oxidative stress by decreasing ROS levels and regulating Nrf2 expressions [7] (Table 1). …”
Section: Modes Of Action Of Probiotic Bacteria In Antioxidationmentioning
confidence: 98%
See 2 more Smart Citations
“…This in turn triggers Nrf2 translocation to regulate expression of cellular antioxidant enzymes, including SOD and HO-1. Bacillus amyloliquefaciens SC06 has also been reported to increase the level of CAT and activate the Nrf2/Keap1 signaling pathway to boost cellular antioxidant status [41]. Further studies are required to confirm the involvement of Nrf2/Keap1 signaling in L. plantarum K2-and K6-induced effects.…”
Section: Discussionmentioning
confidence: 99%